GFP as potential cellular viscosimeter. (18th August 2016) - Visser, Antonie J W G; Westphal, Adrie H; Skakun, Victor V; Borst, Jan Willem
Abstract: The molecular dimensions of proteins such as green fluorescent protein (GFP) are large as compared to the ones of solvents like water or glycerol. The microscopic viscosity, which determines the resistance to diffusion of, e.g. GFP, is then the same as that determined from the resistance of the solvent to flow, which is known as macroscopic viscosity. GFP in water/glycerol mixtures senses this macroscopic viscosity, because the translational and rotational diffusion coefficients are proportional to the reciprocal value of the viscosity as predicted by the Stokes–Einstein equations. To test this hypothesis, we have performed time-resolved fluorescence anisotropy (reporting on rotational diffusion) and fluorescence correlation spectroscopy (reporting on translational diffusion) experiments of GFP in water/glycerol mixtures. When the solvent also contains macromolecules of similar or larger dimensions as GFP, the microscopic and macroscopic viscosities can be markedly different and the Stokes–Einstein relations must be adapted. It was established from previous dynamic fluorescence spectroscopy observations of diffusing proteins with dextran polysaccharides as co-solvents (Lavalette et al 2006 Eur. Biophys. J .35 517–22), that rotation and translation sense a different microscopic viscosity, in which the one arising from rotation is always less than that from translation. A microscopic viscosity parameter is defined that depends on scaling factors between GFP and its immediate environment. The direct consequence is discussed for two reported diffusion coefficients of GFP in living cells.